خاندانی نظام کے استحکام میں اسلامی تعلیمات کا کردار: ایک موضوعاتی و تجزیاتی مطالعہ: The Role of Islamic Teachings in Strengthening the Family System: A Thematic and Analytical Study - Muhammad Athar Rafique; Muhammad Ibrahim (Al-Amīr Research Journal for Islamic Studies, 2025)
The family system is a fundamental element of stability in any society. In the present era, the growing issues of disruption and disintegration within family systems have emphasized the need for deep attention to this matter. The primary question of this study is: What is the role of Islamic teachings in the stability and reform of the family system, and how can they help address the challenges of modern times. The study aims to highlight the significance of the family system. This will shed light on the principles of family relationships in the context of Islamic teachings, providing practical suggestions for implementing these teachings in one’s life. It will address the challenges faced by the family in modern times, such as separation, lack of respect for parents, and inadequate upbringing of children, along with their causes and solutions. The study will conclude that Islamic teachings offer comprehensive principles for the stability of the family system, emphasizing justice, love, patience, and the fair distribution of rights and responsibilities. Islam gives clear guidelines on marriage, divorce, inheritance, and the upbringing of children. These teachings not only strengthen family relationships but also contribute to the establishment of a peaceful and balanced society. An analytical method will be adopted in this research, incorporating references from the Quran and authentic ahadees, writings of Islamic scholars, and studies on contemporary issues. This research will highlight the necessity of adoption of the Islamic teachings in one’s life. Keywords: Islamic family system, parent’s rights, children rights.